2019
DOI: 10.18488/journal.8.2019.71.27.44
|View full text |Cite
|
Sign up to set email alerts
|

Causality between Tourism and Foreign Direct Investment: An Empirical Evidence from Pakistan

Abstract: This study explores the relationship of tourism and FDI inflows along with macro-economic variables in Pakistan over the period ranging from 1979 to 2017. Augmented Dickey-Fuller test results indicate the presence of stationarity in all variables at first difference. Johansen co-integration, VEC model and VECM Granger causality techniques are employed to check short-run and the long-run relationship among the variables. The results of the Johansen co-integration test indicate that FDI, tourism, GDP, exchange r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 49 publications
4
24
1
Order By: Relevance
“…Toda Yamamoto causality provides support to the findings of Lean and Smyth (2010) and Tang (2008) for Malaysia, Shahbaz and Leen (2012) for Pakistan. This study contradicts the results in long-run causality by Balcilar et al (2019), Jamil and Ahmad (2010); Shahbaz and Faridun (2012); Siddiqui and Siddiqui (2019) for Pakistan. The contradicting results in short-run and long-run causality analysis might be due to the omission of certain variables which are necessary for a dynamic growth model e.g.…”
Section: Further Discussioncontrasting
confidence: 92%
“…Toda Yamamoto causality provides support to the findings of Lean and Smyth (2010) and Tang (2008) for Malaysia, Shahbaz and Leen (2012) for Pakistan. This study contradicts the results in long-run causality by Balcilar et al (2019), Jamil and Ahmad (2010); Shahbaz and Faridun (2012); Siddiqui and Siddiqui (2019) for Pakistan. The contradicting results in short-run and long-run causality analysis might be due to the omission of certain variables which are necessary for a dynamic growth model e.g.…”
Section: Further Discussioncontrasting
confidence: 92%
“…Results showed that tourism sector performance toward the increase of foreign direct investment and employment generation has reduced from 2013 and 2017. Siddiqui and Siddiqui (2019) analyzed the association among FDI, inflation, exchange rate, GDP, trade openness, and tourism in Pakistan from 1979 to 2017. Results depicted the presence of unidirectional causality from tourism to FDI and trade openness as well as from inflation and GDP to tourism, while, FDI did not cause tourism in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results indicate that the tourism index has a significant effect on the short-and long-term simultaneous use of renewable energy. Moreover, our findings explored unidirectional causality from FDI to tourism, unlike the conventional scenario (Ben Jebli et al 2019;Siddiqui and Siddiqui 2019), who revealed that FDI unidirectional causes tourism. The causal results also indicate CO 2 e causes tourism; FDI and renewable energy simultaneously causing income in Pakistan.…”
Section: Granger Causality In the Vecm Frameworkmentioning
confidence: 67%